2015
DOI: 10.1088/0029-5515/55/4/043012
|View full text |Cite
|
Sign up to set email alerts
|

The isotope effect in the RFX-mod experiment

Abstract: The isotope effect in the reversed field pinch magnetic configuration is investigated for the first time comparing hydrogen and deuterium plasmas of the RFX-mod experiment. The picture which emerges has several similarities with the results of tokamak experiments, since plasma properties improve increasing the isotope mass M i . The electron temperature is higher in deuterium than in hydrogen in a large fraction of the plasma volume (r/a<0.9) and the energy confinement time scales ∼M 0.3 i . The particle influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 53 publications
3
17
0
Order By: Relevance
“…The particle influx is significantly reduced and the particle confinement time shows a scaling ∼Mi 0.45 . Such effect on confinement has been mainly associated to the mitigation of transport at the edge, internally to the scrape-off layer where long range correlations have been detected [31]. 3D magnetic fields have been applied both in H and D [32].…”
Section: Internal Transport Barriers and Helical State Formationmentioning
confidence: 99%
“…The particle influx is significantly reduced and the particle confinement time shows a scaling ∼Mi 0.45 . Such effect on confinement has been mainly associated to the mitigation of transport at the edge, internally to the scrape-off layer where long range correlations have been detected [31]. 3D magnetic fields have been applied both in H and D [32].…”
Section: Internal Transport Barriers and Helical State Formationmentioning
confidence: 99%
“…In Tokamaks and RFPs, Deuterium is almost always noted to have better confinement than Hydrogen [1,2]. However, the main scaling law for confinement, so-called Bohm or GyroBohm scaling laws predict that Deuterium should have worse confinement due to a larger gyro-radius [3].…”
Section: Introductionmentioning
confidence: 99%
“…The differences of confinement of H and D plasmas, the so-called "isotope effect" in Tokamaks, reversed-field pinches (RFPs) and Stellarators/Heliotrons has long been a largely theoretically unresolved problem. In Tokamaks and RFPs, Deuterium is almost always noted to have better confinement than Hydrogen [1,2]. However, the main scaling law for confinement, so-called Bohm or Gyro-Bohm scaling laws predict that Deuterium should have worse confinement due to a larger gyro-radius [3].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to what is to be expected from gyro-Bohm classical and neoclassical transport estimates, experiments show that heavier hydrogen isotopes produce enhanced plasma confinement in tokamaks [14,15,16,17]. Recently, improved confinement for increased ion mass has also been observed in a reversed field-pinch configuration [18]. It has been suggested that enhanced shear-flow activity for heavier hydrogen isotopes may suppress edge turbulence favorably.…”
Section: Introductionmentioning
confidence: 99%